KAPASITAS DAYA DUKUNG FISIK DAN LINGKUNGAN OPTIMAL SEBAGAI DAYA DUKUNG KEPARIWISATAAN ALAM YOGYAKARTA UTARA SETELAH PASCAERUPSI MERAPI 2010 - Muhamad Muhamad (Jurnal Kawistara, 2013)
This study is intended to determine how likely the surge of tourists who come to visit the center of touristattraction o????jects s????eci????c in north ????ogyakarta region ????ost-eru????tion after 2010. This was carried out toreduce the excessive density of visitors to the area a tourist attraction after the object after the eruption of2010. A high number of visits directly or indirectly will result in interference with ecosystems, and caneven damage the environment. It is therefore necessary analysis to determine the safety guidelines withregard to the issue. On the other hand, the level of comfort of the travelers will also be reduced if thereis a high density. It is necessary for tolerance analysis and physical competence capacity optimally attourism sites. Results of the analysis showed that the distribution of visitors is uneven and concentratedonly in certain point of tolerance and capacity are very limited physical abilities. The ability of theregion to determine the optimal physical tolerance limits that still allow capacity ????exibly so that its longtermgoals, is the ful????llment of the level of ????exibility and satisfaction for tourists.